Risk factors for the delayed viral clearance in COVID-19 patients - Chen, X.; Hu, W.; Yang, M.; Ling, J.; Zhang, Y.; Deng, L.; Li, J.; Lundkvist, Å.; Lindahl, Johanna F.; Xiong, Y. (Wiley, 2021)
Comorbidities are important for the disease outcome of COVID-19, however, which underlying diseases that contribute the most to aggravate the conditions of COVID-19 patients are still unclear. Viral clearance is the most important laboratory test for defining the recovery of COVID-19 infections. To better understand which underlying diseases that are risk factors for delaying the viral clearance, we retrospectively analyzed 161 COVID-19 clinical cases in the Zhongnan Hospital of Wuhan University, Wuhan, China between January 5 and March 13, 2020. The demographic, clinical and laboratory data, as well as patient treatment records were collected. Univariable and multivariable analysis were performed to explore the association between delayed viral clearance and other factors by using logistic regression. Survival analyses by Kaplan-Meier and Cox regression modeling were employed to identify factors negatively influencing the viral clearance negatively. We found that hypertension and intravenous immunoglobulin adversely affected the time of viral RNA shedding. Hypertension was the most important risk factor to delay the SARS-CoV-2 virus clearance, however, the use of Angiotensin-Converting Enzyme Inhibitors(ACEI)/Angiotensin Receptor Blockers(ARB) did not shorten the time for virus clearance in these hypertensive patients' virus clearance. We conclude that patients having hypertension and intravenous immunoglobulin may delay the viral clearance in COVID-19 patients.